PERLINDUNGAN HUKUM TERHADAP PEMEGANG OBLIGASI DALAM PAILITNYA SUATU PERUSAHAAN PENERBIT OBLIGASI - Bismar Nasution; Windha Windha (TRANSPARENCY, 2014)
A corporation issuing an obligation in generally is requiring a fresh fund in highly quantity, some cases such corporation shall find difficulties to have one single creditor to provide the fund as required. As alternative in solving the problem, urged to issue some sheet obligations. Referring in issuing an obligation, the issuer of such obligation may got bankcruption at any time. In correlating with it, such bearer of obligation need legal protection against the obligations that one owned. In this situation, the bearer of obligation is allowable commit legal action if the bearer of the obligation get no any legal protection upon the obligations as posses. In connecting with the cases as mentioned aforesaid, it is necessary to provide a specific formulation that has been taken as follow : how it legal correlation that may emerge in connecting with issuing obligation, how is bankrupt for any corporation may take place, how is legal protection given on the holder of obligation while taking place a bankrupt for a corporation issuing an obligation. This study adopted a normative law method, in reality  it is recognized a library research. Still, in a study with normative legal provided in process all the data secondary and then use as necessary. This study with result showed clearly that the correlation of law base between the issuer of obligation (emitter) and investor as holder of obligation is a legal connection in debts and credit emerging in the agreement. A bankrupted  of corporation issuing obligation is equally with a corporation in bankrupted as generally, the bankrupted itself is allowable to submit if it has fulfilled the requirements in bankrupted as mentioned in the Article 2 point (1) UUK  and PKPU. A legal protection on the holder of obligation while taking place bankrupted corporation issuing the obligation is certainly a legal protection that should be provided to the creditor concurrent with the protection as provided to the holder of obligation in such case is known minim, in generally it is assumed not conforming with the credit owned by the holder of obligation on the corporation as issuer for such obligation.